Analysis of Clean Water Needs Rural Community Based (A Case Study Hippam Campurrejo Makmur Bojonegoro) - Sulton Arrahman Ali; F.Rooslan Edy Santosa (NAROTAMA UNIVERSITY, Indonesia, 2021)
The problem of providing clean water is currently a special concern for both developed and developing countries. Indonesia as a developing country cannot be separated from the problem of providing clean water for its people. One of the main problems faced is the unavailability of clean water sources, the unequal distribution of clean water services, especially in rural areas and the existing clean water sources have not been utilized optimally.villageCampurrejo subdistrict BojonegoroBojonegoro Regency is in dire need of adequate clean water, because so far residents have had difficulty getting clean water, especially during the dry season, some residents only rely on water in old springs/wells without adequate facilities. The research objectives are, 1) to know the speed ofthe need for clean water in the village of Campurrejo sub-district Bojonegoro, Bojonegoro Regency tohi year 2031, 2) What is the reservoir capacity needed to meet the need for clean water in 2031?. Analysis of the calculation of population growth in the village Campurrejo subdistrict Bojonegoro the author uses the Geometric method. And it can be seen that the population in the village Campurrejo subdistrict Bojonegoro reached 6,829 people, and the water demand in 2031 according to the prediction of the population is 1,105 liters/second, the maximum daily needs is 1,326 liters/second, and the discharge at peak hours is 1,768 liters/second.And the demand for clean water in Campurrejo Village in 2031 according to the prediction of the number of HIPPAM customers is 1,623 liters/second, the maximum daily need is 1,948 liters/second, and water needs at peak hours are 2,567 liters/second. Prediction of the number of customers of HIPPAM